Effect of milk treatment on acidification, physicochemical characteristics, and probiotic cell counts in low fat yogurt - Penna, A. L B [UNESP]; Rao-Gurram, Subba; Barbosa-Cánovas, G. V. (My University, 2007)
The effect of milk treatment (heat, high hydrostatic pressure - HHP, or combined heat and HHP) on acidification, physicochemical characteristics, and probiotic cell counts in low fat yogurt was studied. All samples were analyzed for fermentation time, pH, titratable acidity, total solids, water-holding capacity, syneresis, Hunter L*, a*, and b* values, Streptococcus thermophilus, Lactobacillus delbrueckii ssp bulgaricus, L. acidophilus, and Bifidobacterium longum. The application of HHP combined with thermal treatment resulted in yogurt gels with attractive physicochemical characteristics and high water-holding capacity. In addition to this, the milk treatment did not affect the probiotic bacteria growth. The balance of strains in the starter culture and level of inoculation influenced the yogurt fermentation and properties. The use of combined heat and HHP to treat milk before yogurt fermentation could be an alternative process for obtaining high quality, additive-free healthy products.
Keywords: 61 Yoghurt production (milk treatment, product characteristics); Bacteria (microorganisms); Bifidobacterium longum; Lactobacillus delbrueckii; Streptococcus thermophilus